Development of instrument placement criteria and classification method framework for process industry in Malaysia - Khafiz, Muhammad Naqiuddin (2023)
Instruments are devices that convey real-time information on equipment and piping operation status, such as temperature, flow rate, pressure, and many more Instruments are used heavily across various processing facilities for continuous monitoring, inspection, control, and maintenance to ensure safe and profitable plant operation. As such, physical interaction between human operators and instruments are inevitable. However, there are limited documentations from both academic and industrial standpoints that focus on instrument placement designs with appropriate Human Factors Engineering (HFE) integration to facilitate safe and efficient task activities performed by operators. Hence, this study aims to address the gap by developing Instrument Placement Criteria and Classification Method (IPCCM) framework to assist design engineers in classifying, planning, and designing instrument placements based on their critical function in the process facility to facilitate safe and efficient task activities. This study was conducted in three phases. In Phase 1, the best HFE practices in instrument placement design and challenges to implement them were identified through thematic analysis of literature review, document review, and interview. In Phase 2, a preliminary IPCCM framework was developed through thematic analysis of document review, interview, and verified through Focus Group Discussion (FGD). In Phase 3, the verified IPCCM framework was reviewed and validated by industrial experts using Fuzzy Delphi Method (FDM) analysis. Overall, findings from Phase 1 indicate that there are several challenges faced by industrial practitioners to implement best HFE practices in instrument placement designs which permits for potential rooms of improvements during facility design process. Results from Phase 2 reveal 6 criteria that influence instrument placement design in process facility: (1) function in process control, (2) frequency of access during operation, (3) frequency of access during maintenance (4) function in safeguarding, (5) type of activity during access, and (6) type of activity during maintenance. These criteria consist of multiple sub-criteria that can be classified into 3 instrument criticality levels: Category 1 (Very critical), Category 2 (Critical), and Category 3 (Not critical). Following this framework, instruments can be designed and placed according to their criticality level. Validation conducted in Phase 3 shows promising agreement rating on the proposed IPCCM framework in terms of (1) criteria that influence instrument placement, (2) instrument classification method, and (3) the resulting placement design requirement. In conclusion, the validated IPCCM framework is expected to assist in closing the identified gaps and aid design engineers in improving instrument placement design process and quality for process facility development in Malaysia.